A Randomized Controlled Trial Comparing Two Different Antibiotic Regimens for Prophylaxis at Cesarean Section - Kamilya, Gourisankar (Springer-Verlag, 2012)
OBJECTIVES: To compare the efficacy of intravenous single dose, less costly cefotaxime and more expensive amoxycillin–clavulanic acid combination for prophylaxis at cesarean section. METHOD: A double blind randomized controlled trial was undertaken on 760 subjects with two parallel treatment groups. Data were analyzed using Graphpad Instat 3 McIntosh software by Student’s t test, Mann–Whitney U test, the Chi-squared test or fisher’s exact test. RESULTS: Comparatively narrow spectrum low cost cefotaxime is as effective as more expensive commonly used amoxicillin–clavulanic acid with no significant difference of infectious morbidity and hospital stay (p = 0.27 and 0.11 in elective and emergency cases respectively). CONCLUSION: Less costly cefotaxime should be preferred compared to more costly amoxicillin–clavulanic acid combination for prophylaxis at cesarean section.